RELATIONSHIP OF WORK STATUS WITH COMPLETENESS OF BASIC IMMUNIZATION IN INFANTS IN THE WORKING AREA OF THE PUSKESMAS BOTANIA - Ferry Daniel Martinus Sihombing; Omar Sazaly Aldy (Universitas Batam, 2021)
Background :In Indonesia experienced a very worrying Extraordinary Event (KLB), namely the incidence of Diphtheria. Diphtheria incidence in Indonesia has always fluctuated since the 1980s. In 2007 there were 183 cases of diphtheria which increased to 1,192 cases in 2012 and decreased incidence of diphtheria in 2013-2016 (Sariadji, 2017). And according to the Indonesian Pediatrician Association (IDAI), the diphtheria outbreak in Indonesia is the highest in the world. Diphtheria outbreaks occurred in 28 provinces and 142 districts / cities. So there has never been the most in the world and the coverage is 28 Provinces,